Why Is Bank Debt Senior? A Theory of Asymmetry and Claim Priority Based on Influence Costs - Welch, Ivo (Review of Financial Studies, 1997)
This theory can explain why bank debt is universally senior, consistent with the presence of conflict lawyers) and absolute priority violations in financial distress: better organized banks would more strongly contest priority in financial distress if they were junior. Because "deterrence can reduce creditors' total expenses in a priority contest, the ex post stronger lobbyist/litigant should be senior ex ante. For equivalent reasons, the theory can advise when public debt should be senior to trade credit and/or implicit contracts, and can even suggest one rationale for the absolute priority rule (APR). This article further shows that Chapter HI creditor reimbursement procedures can lower overall costs. Article published by Oxford University Press on behalf of the Society for Financial Studies in its journal, The Review of Financial Studies.